«Duas cartas unius tenoris per alphabetum divisas scripsi». Contributo a una geografia delle pratiche documentarie nell'Italia dei secoli XII e XIII - Carbonetti Vendittelli, Cristina (Scrineum, 2013)
This study is inspired by the recent finding of some chartae partitae from the decades between the twelfth and thirteenth centuries preserved in the City Library and in the Diocesan Historical Archive of Viterbo and by the consequent discovery of a documentary phenomenon never noted by scholars until now for this city. As well as studying this particular documentary and unknown practice of the notaries of Viterbo, the Author extends the focus on the Italian panorama, comparing  the case of Viterbo with those of Piedmont, Liguria and Sicily, where in the same centuries notaries used this documentary form for legal acts such as agreements, conventions, treaties and other bilateral actions, analyzing the reasons that led to the notaries of these different historical areas to use the charta partita, and identifying three different documentary areas inside which it was employed: the public one, the mercantile one and that of the instrumentum publicum. Finally, the Author considers in what way the words cyrographum, charta (or instrumentum) per alphabetum (or per ABC) partita (or partitum) were used in Italian documents. The artiche gives also, for the first time, the critical edition of five previously unpublished documents and an analytical description of the external features of all.